2005
DOI: 10.1177/0885066605275314
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Morbid Obesity in the Intensive Care Unit

Abstract: This was a retrospective chart review of consecutive obese patients admitted to the medical intensive care unit. Patients were divided into 2 groups: mild to moderately obese (group 1, body mass index =30-40 kg/m(2)) and morbidly obese (group 2, body mass index >40 kg/m(2)). Acute Physiology and Chronic Health Evaluation II scores were not significantly different between the 2 groups. Morbidly obese patients (group 2) had higher rates of mortality and nursing home admission. They also showed higher rates of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 47 publications
1
70
1
1
Order By: Relevance
“…The literature to date with patients with BMI Ն 40 kg/m 2 examined as a cohort is quite variable, with some studies showing no difference in ICU outcomes and mortality, 4,5 others reporting improved mortality, [6][7][8] and others fi nding longer ICU LOS, increased DMV, and increased mortality. [14][15][16] One metaanalysis from 2009 aggregating 23 studies found extremely obese patients as a group had similar hospital mortality (relative risk, 0.83; 95% CI, 0.66-1.04), a trend toward longer ICU and hospital stays, and no difference in DMV compared with patients of normal weight. 17 A recent study found that patients who had 2009 infl uenza A(H1N1) who were obese had a longer DMV, ICU LOS, and hospital LOS without a difference in mortality.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature to date with patients with BMI Ն 40 kg/m 2 examined as a cohort is quite variable, with some studies showing no difference in ICU outcomes and mortality, 4,5 others reporting improved mortality, [6][7][8] and others fi nding longer ICU LOS, increased DMV, and increased mortality. [14][15][16] One metaanalysis from 2009 aggregating 23 studies found extremely obese patients as a group had similar hospital mortality (relative risk, 0.83; 95% CI, 0.66-1.04), a trend toward longer ICU and hospital stays, and no difference in DMV compared with patients of normal weight. 17 A recent study found that patients who had 2009 infl uenza A(H1N1) who were obese had a longer DMV, ICU LOS, and hospital LOS without a difference in mortality.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…[6][7][8] Other studies found that obese and extremely obese patients may have longer ICU and hospital LOS, duration of mechanical ventilation (DMV), and increased mortality. [9][10][11][12][13][14][15][16] A recent meta-analysis reported that extremely obese patients with a BMI Ն 40 kg/m 2 had decreased hospital mortality compared with normal-weight patients, but this did not reach statistical signifi cance (relative risk, 0.83; 95% CI, 0.66-1.04). 17 Additionally, a recent study reported that mortality in critically ill patients who have a BMI Ն 35 kg/m 2 was improved among those who received adequate nutrition (energy and protein).…”
mentioning
confidence: 99%
“…Patients with morbid obesity may be at higher risk for these infections 33 than are nonobese patients, and the higher risk may be partly due to the immune dysfunction associated with morbid obesity. 34 However, the results of a recent study 35 did not indicate any difference in the rates of central catheter-associated bloodstream infections between obese and nonobese patients.…”
Section: C: Circulationmentioning
confidence: 99%
“…11,12 The results from previous studies and three meta-analyses addressing this topic [13][14][15] have mostly been from mixed medical-surgical ICU populations [13][14][15][16][17][18] and did not include a subgroup analysis by race or the type of ICU (trauma, surgical vs medical) to which patients were admitted. In studies including only patients admitted to medical ICUs (MICU), some lacked appropriate non-obese comparison, 19,20 others used a different definition of obesity 21 or included only limited BMI groups. 24 Laboratory values used were those obtained within 24 hours of admission.…”
Section: Introductionmentioning
confidence: 99%